Konsekuensi Pandangan pada Harga, Mutu Produk dan Lokasi pada Keputusan Pembelian: Studi Kasus Warung Makan Bu Jum Malangsari - Nia Widiana Ratri; Susanto Susanto (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
This study examines the impact of location, product quality, and price perception on decisions to buy at Warung Makan Gado-Gado Bu Jum in Malangsari. Determining the degree to which location, product quality, and price perception influence decisions to buy at Warung Makan Gado-Gado Bu Jum in Malangsari is the aim of this study. This study's data was gathered via a questionnaire that employed a Likert scale for measuring. Purposive sampling was used to choose 96 respondents who had made purchases from Warung Makan Gado-Gado Bu Jum in Malangsari while taking specific factors into account. Using SPSS version 25, the data analysis method employs multiple linear regression analysis, validity testing, trustworthiness testing, and traditional hypothesis testing. Price perception (X1), product quality (X2), and location (X3) all have a positive and significant impact on purchase decisions (Y), according to the research findings. This suggests that both price perception and location may improve the choices made when making purchases at Bu Jum's Gado-Gado restaurant in Malangsari. As indicated by the coefficient of determination (R2) of 0.736, location, product quality, and price perception account for 73.6% of the purchase decision variable, with other factors influencing the remaining 26.4%.